Aplicación de estrategias lúdicas para el desarrollo de las inteligencias emocional y naturalista, en los niños del grado tercero en el área de ciencias naturales de la institución educativa los Quindos de Armenia Quindío (2012)
Applying playful strategies in the classroom to the development of emotional intelligence and naturalist optimizes learning and intrapersonal and interpersonal development in third grade children in the school The Quindos. This is verified by comparing the results of the pre -test and post -test applied to children in group A (group in which the work was done) and the results of the pre -test and post -test in group B (group which contrasts), where the result shows that both the emotional test, naturalist and knowledge, even gets increased, indicating that if children improve learning. The tests are applied: the test that values emotional self-awareness, self-control, emotional achievement, empathy and social skills, the test applies based naturalist Flores (1990) and the knowledge test for Unit 2 "humans "I made the researchers work. The playful strategies applied in the treatment group are group and individual workshops are held, exhibitions, visits, work anywhere, cutting, gluing and drawing, which increase the emotional and naturalist intelligences and knowledge in children.